Postauricular sinus: a case report - Sahoo, Soumick R.; Nayak, Pallavi; Datta, Nilanjan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Post auricular sinus is a rare variant of the preauricular sinus in which sinus opening is located posterior to the tragus. Surgical excision of the sinus tract with its branches should be done in cases presenting with recurrent infections. There are 2 approaches unidirectional and bidirectional and the choice of approach depends on the preference of the surgeon. In our case right side post-auricular sinus was noted in a 35-year-old male which was surgically excised by unidirectional approach.